Multiple Intelligences Based Learning through Practical Work to Investigate Students’ Scientific Process Skills and Concept Understanding of Spermatophyta in Upper Secondary School - Elin Nailur Rahmah; Siti Sriyati (Universitas Sebelas Maret, 2015)
This study aims to investigate the effects of multiple intelligences based learning through practical work to investigate student’s Scientific Process Skills and concept understanding of Spermatophyte in Upper Secondary School. This quasi experiment study used pretest-posttest control group design with a cluster random sampling in MA As-Sa’adah Sukasari Sumedang. A total of 64 students of Grade 10 from two classes (Experiment class N=32 and Control class N= 32) participated in the study. Some instruments were involved in this study such as: (1) Pre test and post test to measure students’ Scientific Process Skills; (2) Pre test and post test to measure students’ concept understanding; (3) Students’ Questionnaire; and (4) Observation sheet. The data was analysed by SPSS 20 Program to test the normality, homogeneity, and t-test. The results showed that there is a significant difference of students’ Scientific Process Skills and concept understanding post test in experiment class and control class showed with tcount 3,02 and P value 0,004 < α= 0,05 for Scientific Process Skills, because of P value < α= 0,05 so H0 is rejected and H1 is accepted meaning that Scientific Process Skills in experiment class and control class is a significant difference, then result showed with tcount 3,43 and P value 0,001< α= 0,05 for concept understanding, because of P value < α= 0,05 so the conclusion obtained H0 is rejected and H1 is accepted meaning that concept understanding in experiment class and control class is a significant difference. It showed that multiple intelligences based learning through practical work is significantly affect students’ scientific process skills and concept understanding. Most of students also give positive responses to multiple intelligences based learning through practical work.Keywords: Multiple Intelligences Based Learning, Practical Work, Scientific Process Skills, Concept Understanding, Spermatophyta